The Central Industrial District as an Example of the Sociological Imagination of its Creators - Piotr Zawada (The Francis de Sales Scientific Society (TNFS.PL), 2022)
In defining the place and significance of the Central Industrial District (COP) in Polish history and economy, it is impossible to overlook the numerous components of this complex economic undertaking, the plan whose main purpose was to increase the level of defence capabilities of the Second Polish Republic and to offset the differences in the economic sphere of particular areas of Poland. In addition to a few historical issues, the article presents the achievements of the Aviation Valley, an association listed among the key national clusters, created as a result of a specific organizational culture implemented in Sub-Carpathian Region since the beginning of the COP.